CONCEPTS AND PRACTICES OF INTERCULTURAL COMMUNICATION IN THEDEVELOPMENT OF INTERNATIONAL ECONOMIC RELATIONS - AKSYONOVA, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In today’s globalization environment, intercultural communication plays a crucial role in shaping effective international economic relations. Taking into account the cultural characteristics of partners, adapting communication strategies, and integrating international standards of business ethics are key factors for successful cooperation at the global level. The study shows that companies that pay attention to intercultural aspects of interaction achieve greater long-term efficiency and competitiveness. Based on the analysis of the activities of international corporations such as McDonald’s and Toyota, it was found that adaptive business strategies contribute to the successful entry into new markets and strengthening consumer trust. Localization of business models, taking into account traditions, customs, and language features of target audiences allow companies to minimize the risks of misunderstanding and cultural conflicts. The implementation of effective intercultural strategies ensures the stability of economic relations and helps strengthen partnerships between international business entities. At the same time, globalization processes create new challenges for intercultural communication, which require appropriate adaptive solutions. In particular, the digital transformation of business communication, management of multicultural teams and overcoming language barriers are becoming priority tasks for international corporations. The use of modern digital technologies, in particular artificial intelligence and automated translation systems, allows to increase the efficiency of international communication processes and reduce the risks of intercultural misunderstandings. Further research should be aimed at studying the mechanisms of adaptation of international business to cultural diversity, the impact of digital technologies on intercultural interaction and the development of new strategies for managing intercultural communications. Of particular relevance is the study of methods for forming intercultural competence of managers and specialists in the field of international business. Thus, the development of intercultural communication strategies in the context of globalization is an important area of ​​scientific research that will contribute to increasing the competitiveness of companies, strengthening international cooperation and harmonious economic integration. Studying this phenomenon will allow optimizing communication processes between representatives of different cultures and creating effective mechanisms of interaction in the field of international economics.